Catalytic Antisense DNA Molecules Targeting Egr-1 Inhibit Neointima Formation following Permanent Ligation of Rat Common Carotid Arteries - Lowe, Harry C.; Chesterman, Colin N.; Khachigian, Levon M. (Thrombosis and Haemostasis, 2002)
Animal models of neointima (NI) formation have proven useful in gaining insights into the mechanisms of restenosis after coronary angioplasty and stenting, but the events at a molecular level remain incompletely understood. Here, we describe a technically straightforward, rat model of NI formation, involving complete ligation of the common carotid artery and demonstrate the importance of the immediate-early gene and zinc finger transcription factor Egr-1 in this process. Acute cessation of common carotid blood flow by vessel ligation, was followed by the expression of Egr-1 in the arterial media within 3 h and NI formation proximal to the point of ligation at 18 days. Local delivery of catalytic oligodeoxynucleotides (ODN) targeting rat Egr-1 mRNA at the time of ligation reduced both Egr-1 expression and NI formation in this model. In contrast, a scrambled version of this ODN had no inhibitory effect. These studies demonstrate for the first time that arterial intimal thickening following artery ligation is critically-dependent on the activation of Egr-1.
Keywords: Neointima; Egr-1; oligonucleotide